# Aptitude - Square Root and Cube Root - Discussion

Discussion Forum : Square Root and Cube Root - General Questions (Q.No. 6)
6.

If a = 0.1039, then the value of 4a2 - 4a + 1 + 3a is:

0.1039
0.2078
1.1039
2.1039
Explanation:

4a2 - 4a + 1 + 3a = (1)2 + (2a)2 - 2 x 1 x 2a + 3a

= (1 - 2a)2 + 3a

= (1 - 2a) + 3a

= (1 + a)

= (1 + 0.1039)

= 1.1039

Discussion:
70 comments Page 2 of 7.

While I am solving getting (2a-1) or we can write (1-2a) also but why answer differs I mean according to options we should change ?

Krishna nice explanation.

I do agree with krishan, however 2a-1 is not equal to 1-2a because the value may be the same however, is it postive or negitive value, so can anyone explain on this?

4a2 - 4a + 1

(2a)2 - 2(2a)(1) + (1)2

(2a - 1)2

so, 2a - 1 + 3a

Why 1 - 2a is here ???

I agree with those who has a doubt as why it won't be (2a-1)^2. should we change our ans according to the options available???

Mannoj kumar said:   1 decade ago
I agree with sayani. We need to see the options also.

Who goes for the answer anyone solving this would go for the formula asq - 2ab + bsq which will give (2a - 1)sq.

I don't think (1-2a)sq can be the way out.

I have the same doubt, why cant it be (2a-1)2.

sqrt(4a2-4a+1)=2a-1 or 1-2a?

Your ans is right. But according to KRISHNA ,the sqrt of (2a-1)^2 is +(2a-1) and -(2a-1).so if we choose -(2a-1) then we get

-(2a-1)+3a=-2a+1+3a
=a+1
=.1039+1=1.1039 (ans)

So, this is the technique to SATISFY the option, that has given in the question.